A Secure Cloud Storage Retrieval using Cost Based Iterative Deepening Depth-First Search Algorithm - et al., Tunuguntla Kishore Babu (International Journal of Advanced Science and Technology, 2019)
Nowadays, cloud storage is a popular service for many data owners due to its advantage of high scalability and large-scale storing ability. Data users can utilize its open and highly scalable application interface to store files, pictures, videos, etc. But the data security includes integrity, availability and confidentiality of data has been found to be a major challenge in cloud systems and also it is a main reason why companies avoid cloud service usage. Researchers have been studying the authentication mechanisms for cloud data integrity. This research work focuses on efficient search on the encrypted data so that the cloud auditor does not have knowledge of any query information. An efficient cryptographic algorithm is developed in this study to secure the owner’s data. Then, Cost based Iterative Deepening Depth-First Search (CIDDFS) algorithm is designed to reduce the searching time of the keyword in encrypted data. The usage of the cosine similarity of the text reduced the cost of searching time. The experimental analysis stated that when the file size is 512kB, the proposed method achieved 93ms encryption time, 68ms decryption time and 62ms searching time while comparing with existing techniques: Depth First Search (DFS) and Breadth First Search Algorithm (BFS).